Optimizing the performance of hybrid renewable energy systems to accelerate a sustainable energy transition in Nigeria: A case study of a rural healthcare centre in Kano. (September 2022) - Yakub, Abdulfatai Olatunji; Same, Noel Ngando; Owolabi, Abdulhameed Babatunde; Nsafon, Benyoh Emmanuel Kigha; Suh, Dongjun; Huh, Jeung-Soo
Abstract: The COVID-19 pandemic brought tremendous pressure to the African continent's health sector, particularly in rural areas. Rural healthcare facilities experienced severe energy shortages due to the influx of Covid-19 patients, which strained their operating capacities. These facilities usually rely on diesel engines, and this unidirectional approach limited governments' vision in resolving the energy crisis. This paper aims to develop a hybrid energy system (HES) that combines alternate energy sources available at a rural healthcare centre in northern Nigeria and conduct a techno-economic analysis of the viability of such systems. The energy potential of available energy resources at the target location and comparison of various HES configurations were estimated with HOMER Pro software to determine the most feasible choices. These choices were analyzed for technical, financial, and environmental viability using RETScreen Expert. Due to an abundance of solar energy, low diesel cost, and sufficient wind energy potential, the results show PV – Diesel and Wind – Diesel system HES configurations as the only practical choices. Techno-economic analysis indicates that the PV – Diesel HES produces annual savings of $30, 583 with a Net Present Value (NPV) of $390, 949 compared to $15, 174 and $193, 980 for the Wind – Diesel configuration. Further analysis solidifies the PV-Diesel HES as the best choice with a payback period of 1.3 years, 75 tons of CO2 emission reduction, and annual savings of $30, 583 compared to the initial diesel energy system. Highlights: Many local community health clinics across Africa suffer from energy problems. COVID-19 pandemic has brought pressure to the African continent's health sector. HOMER was used to optimize different hybrid energy system configurations. Combination of RETScreen and HOMER for modelling HES in the health sector. RETScreen was used to carry out risk analysis for the PV-Diesel combination.